Intensitas Curah Hujan Memicu Tanah Longsor Dangkal di Sulawesi Selatan - Hasnawir (Jurnal Penelitian Kehutanan Wallacea, 2012)
The rainfall induced landslides including shallow landslides have resulted in substantial property damage as well as loss of human lives. In recent years, the South Sulawesi province has been affected by numerous shallow landslide phenomena caused by particularly intense rains. The main objective of this study was to analyze the shallow landslides caused by intense rain that took place between 3rd and 4th May 2011 in the province of South Sulawesi and to determine rainfall thresholds for shallow landslides warning. The findings showed that rainfall intensity over 50 mm/hr might cause shallow landslides that could cause damage to property including loss of human lives. The threshold, as defined by the lower boundary of the points representing shallow landslides-triggering rainfall events, is expressed as I=52D-0.79. The threshold rainfall for shallow landslides could be very important information to develop the warning system in the study area.